“Look not thou upon the wine…”. Wine Drinking in Proverbs 23:19–35 in Light of the Book of Sirach - Klaiman, Asnat (The Biblical Annals, 2024)
This article examines the motif of wine drinking in didactic biblical wisdom literature from a synchronic perspective, using an analogy between two textual units in the Book of Proverbs in light of the Book of Sirach. The complex literary and social functions of the motif of wine drinking and its significance for ancient Israelite society are examined. The first part of the article focuses on Prov 23, which presents the didactic wisdom approach to drinking wine, consisting mainly of warnings and cautions to youth regarding wine and its consequences for the community. The second part compares this didactic approach to the hybrid approach of the Book of Sirach, where didactic precepts appear beside a cultural portrayal of wine drinking as a joyful and accepted tradition. The author of this article claims that this complex attitude is rooted in using the wine-drinking motif in biblical wisdom literature to reflect the social reality in ancient Israel.